2021
DOI: 10.1177/03611981211006111
|View full text |Cite
|
Sign up to set email alerts
|

Stop Sign Gap Assist Application in a Connected Vehicle Simulation Environment

Abstract: Assessment of the safety and mobility impacts of connected vehicles (CVs) and cooperative automated vehicle applications is critical to the success of these applications. In many cases, there may be trade-offs in the mobility and safety impacts depending on the setting of the parameters of the applications. This study developed a method to evaluate the safety and mobility benefits of the Stop Sign Gap Assist (SSGA) system, a CV-based application at unsignalized intersections, which utilizes a calibrated micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…With the help of sensing devices, users can interact with virtual environments. is technology is used in the industrial field to build virtual parts models before production [6]. Virtual reality technology is mainly used in the field of computer 3D simulation, which integrates various information about products and realizes the dynamic design of products in 3D view.…”
Section: Introductionmentioning
confidence: 99%
“…With the help of sensing devices, users can interact with virtual environments. is technology is used in the industrial field to build virtual parts models before production [6]. Virtual reality technology is mainly used in the field of computer 3D simulation, which integrates various information about products and realizes the dynamic design of products in 3D view.…”
Section: Introductionmentioning
confidence: 99%
“…These simulation-based studies concluded that CV environments can simultaneously provide positive effects on mobility and safety. Traffic simulation has been utilized to evaluate the effectiveness of warning information not only for driving safety, but also traffic flow performance [14][15][16]. Sharma et al (2021) showed that in mixed traffic conditions, CVs improve the efficiency and safety of traffic flow [17].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results showed that the impact of SLTA could be beneficial with respect to increasing the left-turn capacity and safety, as well as reducing the delay time, depending on the SLTA gap time parameter setting. Further, Arafat et al ( 33 ) evaluated the impact of the Stop Sign Gap Assist (SSGA) system, a CV-based application at unsignalized intersections, on the mobility and safety performance of an intersection using a calibrated microscopic simulation model. Their study demonstrated a clear trade-off between safety and capacity.…”
Section: Literature Reviewmentioning
confidence: 99%